Polymerization-Induced Self-Assembly (PISA) Using ICAR ATRP at Low Catalyst Concentration - Wang, Guowei; Schmitt, Michael; Wang, Zongyu; Lee, Bongjoon; Pan, Xiangcheng; Fu, Liye; Yan, Jiajun; Li, Sipei; Xie, Guojun; Bockstaller, Michael R; Matyjaszewski, Krzysztof (Macromolecules, 2016)
Polymerization-induced self-assembly (PISA) was achieved by conducting an initiators for continuous activator regeneration atom transfer radical polymerization (ICAR ATRP) at low ppm of copper catalyst concentration. A poly(oligo(ethylene oxide) methyl ether methacrylate)50 (POEOMA50) macroinitiator and stabilizer was synthesized by an aqueous ICAR ATRP using CuIICl2/tris(pyridin-2-ylmethyl)amine (TPMA) complex. Subsequently, the dispersion polymerization of benzyl methacrylate (BnMA) in ethanol was realized with a CuIIBr2/TPMA complex either at room temperature or at 65 °C using V-70 or AIBN as radical initiators, respectively. The effect of catalyst concentration, radical initiators, targeted degree of polymerization (DP) of PBnMA, solids content, and temperature on the molecular characteristics and self-assembly behavior of block copolymers POEOMA–PBnMA was evaluated by gel permeation chromatography (GPC), transmission electron microscopy (TEM), and dynamic light scattering (DLS). Block copolymers assembled into spheres, wormlike aggregates, and vesicles with diameters ranging from 100 to 600 nm, depending on the temperature, solids content, and the DP of PBnMA. The effect of the temperature on the polymerization behavior and morphological evolution was attributed to the temperature-dependent plasticization of the core-forming PBnMA block above and below its glass transition temperature (T g = 54 °C).